Computational analysis and molecular dynamics of natural anthelmintic compounds from Algerian herbal sources - Farouk BOUDOU; Amal BELAKREDAR; Alaeddine BERKANE; Mohammed RASHEED (Notulae Scientia Biologicae)
It is crucial to underline the necessity of discovering new sources of natural compounds with antiparasitic action in light of the scarcity of new anthelmintic medications on the market, as well as the issue of developing parasite resistance to conventional medications. Indeed, computer-aided design is the initial step in the screening of new inhibitors. In silico screening for drug-likeness prediction, toxicity risk assessment (mutagenic, tumorigenic, irritant, or effects on reproduction), molecular docking, and molecular dynamics targeting β-tubulin, a key protein in the cellular functions of helminths, has been performed on 33 phytochemical compounds belonging to 20 different plants used in Algerian folk medicine to treat gastrointestinal disorders. Among the tested compounds, only 15 met the drug-likeness prediction criteria according to Lipinski’s Rule of Five and Ghose’s filter. Seven of them showed no adverse effects in the toxicity risk assessment. Notably, only luteolin from Teucrium polium L. exhibited the lowest binding energy (-8.2 kcal/mol), outperforming not only the other compounds but also the standard drug albendazole (-5.6 kcal/mol), and showed good affinity toward the protein active pocket and conformational stability during molecular dynamics simulations for 250 ns. It was found that plant substances such as luteolin possess the best pharmacological and toxicological qualities and inhibitory activity against β-tubulin, and can be considered promising candidates for high-value anthelmintic drugs.